Cost–effectiveness of a FISH assay for the diagnosis of melanoma in the USA. (June 2013) - Kansal, Anuraag R; Shaul, Alissa J; Stern, Sean; Busam, Klaus; Doucet, Cynthia A; Chalfin, Donald B
Objective : The authors evaluated the cost–effectiveness of a FISH assay in melanoma diagnosis in the USA.Method : A model was developed simulating the addition of FISH to the diagnosis of suspected melanoma. A decision analytic module simulated diagnosis using microscopic assessment alone versus addition of FISH (sensitivity: 92%; specificity: 94%). The authors simulated a clinical setting in which an initial excisional biopsy microscopic assessment (sensitivity: 73%; specificity: 78%) was followed by dermatopathologist assessment (sensitivity: 89%; specificity: 79%) for inconclusive results. Diagnostic strategies 1 and 2 added FISH to the initial and dermatopathologist assessments, respectively. A Markov outcomes module simulated patients' remaining lifetime, including treatment.Results : In diagnostic strategies 1 and 2, the cost per quality-adjusted life year gained was US14, 930 and 43, 925, respectively, versus no FISH. Cost per misdiagnosis avoided was US3292 and 3759, respectively. Sensitivity and specificity without FISH were both ≥88%; however, addition of FISH exceeded US100, 000/quality-adjusted life year.Conclusion : In specific clinical settings, FISH could be cost effective for melanoma diagnosis.